Developing the skills for complex thinking research: a case study using social robotics to produce scientific papers - Lopez-Caudana, Edgar Omar; George-Reyes, Carlos Enrique; Avello-Martínez, Raidell (Frontiers in Education, 2024)
The development of university students' skills to successfully produce scientific documents has been a recurring topic of study in academia. This paper analyzes the implementation of a training experience using a digital environment mediated by video content materials starring humanoid robots. The research aimed to scale complex thinking and its subcompetencies as a hinge to strengthen basic academic research skills. Students from Colombia, Ecuador, and Mexico committed to preparing a scientific document as part of their professional training participated. A pretest to know their initial level of perception, a posttest to evaluate if there was a change, and a scientific document the students delivered at the end of the training experience comprised the methodology to demonstrate the improvement of their skills. The results indicated students' perceived improvement in the sub-competencies of systemic, creative, scientific, and innovative thinking; however, their perceptions did not align with that of the tutor who reviewed the delivered scientific product. The conclusion was that although the training experience helped strengthen the students' skills, variables that are determinants for a student to develop the knowledge necessary to prepare scientific documents and their derived products remain to be analyzed.